Nurturing future Engineers through Industry-Oriented Training: The imperative of Core Competencies - Toney, Glenson; Roopesh; Bhat, Sathyendra; Kaliveer, Vinoothan; K G, Binu; D’Silva, Rolvin; K, Yathish Kumar; Shetty, Ashwin; Singh, Athokpam Bikramjit (Journal of Engineering Education Transformations, 2025)
This research paper investigates the transformative effects of Industry-Oriented Training (IOT) at St Joseph Engineering College both on engineering and management graduates. The IOT course under evaluation emphasizes five essential skill sets: communication, self-evaluation, leadership, team building, and problem-solving. The study analyzes the impact of this comprehensive training endeavor on students’ academic performance, employment, and career paths. The findings demonstrate the tangible benefits of the well-planned and structured IOT curriculum. The program’s participants graduate with the critical problem-solving abilities essential for success in challenging work environments. The investigation extends beyond traditional academic metrics to demonstrate the substantial impact of IOT on professional and personal development. This study emphasizes the critical significance of effective communication, the potency of self-evaluation in fostering adaptability, the transformative potential of leadership skills, the value of teamwork in achieving common goals, and the critical significance of problem-solving prowess in addressing contemporary challenges. This study indicates how industry-oriented training acts as a catalyst for holistic growth, enabling students to not only meet but also exceed the expectations of the engineering and management landscape’s constantly evolving expectations. For educators, organizations, and corporations committed to fostering the next generation of dynamic and competent professionals, the paper offers insights that will be invaluable.